2015
DOI: 10.1111/pai.12502
|View full text |Cite
|
Sign up to set email alerts
|

Wheat protein recognition pattern in tolerant and allergic children

Abstract: Children with challenge proven clinical relevant food allergy and tolerant ones had a similar spectrum of IgE binding to the same protein bands. These findings imply that component-resolved diagnostics might not be helpful in the diagnostic work-up of wheat allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
0
9
0
5
Order By: Relevance
“…ImmunoCAP and immunoblot were used for PAMD@ in sera from children with a suspected wheat allergy. 202 Of these children, 44 were reactive and 62 nonreactive to the food challenge. Although the authors confirmed a-, b-, g-, and u-gliadins and low-molecular-weight glutenin as major allergens in terms of IgE binding, these allergens were not able to discriminate the tolerant from the challenge-positive children.…”
Section: Wheatmentioning
confidence: 99%
“…ImmunoCAP and immunoblot were used for PAMD@ in sera from children with a suspected wheat allergy. 202 Of these children, 44 were reactive and 62 nonreactive to the food challenge. Although the authors confirmed a-, b-, g-, and u-gliadins and low-molecular-weight glutenin as major allergens in terms of IgE binding, these allergens were not able to discriminate the tolerant from the challenge-positive children.…”
Section: Wheatmentioning
confidence: 99%
“…Even minor changes in the (developing) barrier function can lead to exposure to luminal antigens in early phases of life and may result in accelerated immunological responses and clinical manifestations, such as allergies in later stages of life. The prevalence of wheat allergy in children is increasing (Cianferoni et al 2013 ; Makela et al 2014 ; Sievers et al 2015 ), and as DON is mainly found in wheat and wheat-derived products, it cannot be excluded that DON plays also a role in the onset of allergic reactions in children. Further studies should be devoted to the effects of frequently occurring mycotoxins in human food supplies on TJ proteins, and their effect on the intestinal barrier should be included in the overall risk assessment of mycotoxins in foods.…”
Section: Clinical Relevance and Conclusionmentioning
confidence: 99%
“…Известно, что пшеница, как и другие продукты, со-держит множество белков -альбумины (растворимые в воде, неродственные альбуминам молока или яйца), глобулины (нерастворимые в воде), глютены, включаю-щие в себя глиадин и глютен -главные белки пшеницы [16,17]. Глиадин -белок, принадлежащий к классу про-ламинов, составляет 28−42%, а глютен -42−62,5% всех белков пшеницы.…”
Section: Discussionunclassified
“…Глиадин -белок, принадлежащий к классу про-ламинов, составляет 28−42%, а глютен -42−62,5% всех белков пшеницы. Проламины присутствуют во всех зла-ках -глиадин (пшеница), секалин (рожь), гордеин (яч-мень), зеин (кукуруза), авенин (овес), орзенин (рис) -и имеют гомологию последовательности аминокислот [16,17]. Широко описаны аллергические реакции, возникаю-щие при употреблении пшеницы [18,19].…”
Section: Discussionunclassified